What drives the demand of monetary financial institutions for domestic government bonds? Empirical evidence on the impact of Basel II and Basel III - Michael Lang; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper examines the treatment of sovereign debt exposure within the Basel framework and measures the impact of bank regulation on the demand of Monetary Financial Institutions (MFI) for marketable sovereign debt. Our results suggest that bank regulation has a significant positive impact on MFI demand for domestic government securities. The results are representative for the MFI in the euro zone. They remain highly robust and significant after controlling for other influential factors and potential endogeneity.
urn:nbn:de:bsz:180-madoc-375230
Keywords: G11; G21; G28; 330; Monetary Financial Institutions; Financial sector regulation; Sovereign bond holdings; Investment incentives